A Family in the Coolie Village, Trinidad - (:unkn) unknown (Muir, Marshall and Co. Ltd., Trinidad, 2008)
A photo of an East Indian family, woman and two children.
Colour: Brown and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; East Indians--Trinidad and Tobago; Trinidad and Tobago; Families--Trinidad and Tobago; Children--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago